Hydrogen evolution and dissolution on graphite electrodes in the electrolysis of molten KHSO4 : I. Kinetics of the reactions on dense graphite - Balskus, Eduardo Juan (1971)
The kinetic parameters obtained under steady and non-steady conditions for cathodic hydrogen evolution and anodic hydrogen dissolution on dense graphite electrodes with molten potassium bisulphate at different temperatures are reported. The anodic E/i curves exhibit a 12 power dependence on hydrogen gas pressure. These results will be compared to those obtained with porous graphite electrodes in Part II of the present research, in an attempt to establish the probable mechanisms of the electrode processes.